2021
DOI: 10.3390/polym13040490
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Functionalization of Graphene Oxide with Fructose, Starch, and Micro-Cellulose by Sonochemistry

Abstract: In this work, we report the synthesis of graphene oxide (GO) nanohybrids with starch, fructose, and micro-cellulose molecules by sonication in an aqueous medium at 90 °C and a short reaction time (30 min). The final product was washed with solvents to extract the nanohybrids and separate them from the organic molecules not grafted onto the GO surface. Nanohybrids were chemically characterized by Fourier-transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), and Raman spectroscopy and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Even though chemical modification alters the strong sp 2 hexagonal structure into a weaker sp 3 structure, experimental studies have shown that it can improve the mechanical and other engineering properties of the produced nanocomposite [28][29][30][31][32][33][34]. This improvement is highly governed by the functional group type, molecular configuration, and concentration [35][36][37][38]. Despite the limited number of studies dedicated to investigating the effect of graphene nanoplatelet functionalization, there is a need for a systematic approach to understanding the role of different types of graphene nanoplatelet modification and functionalization on the resulting composite mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Even though chemical modification alters the strong sp 2 hexagonal structure into a weaker sp 3 structure, experimental studies have shown that it can improve the mechanical and other engineering properties of the produced nanocomposite [28][29][30][31][32][33][34]. This improvement is highly governed by the functional group type, molecular configuration, and concentration [35][36][37][38]. Despite the limited number of studies dedicated to investigating the effect of graphene nanoplatelet functionalization, there is a need for a systematic approach to understanding the role of different types of graphene nanoplatelet modification and functionalization on the resulting composite mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the presence of GO intercalated sheets and their interaction through hydrogen bonds, the retrogradation can be inhibited 33 . Additionally, it was recently found that chemical reactions between starch molecules and oxygen functionalities attached to GO can lead to the partial restoration of the conjugated network of the sp 2 lattice of carbon atoms and, consequently, the recovery of graphene electronic properties (i.e., reduction) 34 , 39 , 40 . The latter is believed to provide for a reduced electrical resistance and an improved electrochemical capacitance of fabricated electrodes 29 , 41 , 42 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the ability of oxygen grups on GO sheets to interact with polymers have been exploited to improve their electrical and mechanical properties, as well as their thermal stability 32 . In particular, biocomposites of starch and GO have recently been investigated [33][34][35] .…”
mentioning
confidence: 99%
“…Ultrasound is characterized as any sound wave in frequencies above the normal hearing range of the human ear (i.e., above 16 kHz) [14] and the field of application of ultrasonic waves is surprisingly vast, such as in the pharmaceutical and food industries [15] , [16] , [17] , [18] , [19] , [20] , extraction processes [16] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , waste treatment [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , materials chemistry [47] , [48] , [49] , analytical chemistry [50] , [51] , [52] , [53] , and nanoparticle synthesis [24] , [41] , [54] , [55] , [56] , [57] , [58] , [59] . All these examples, addressing the application of ultrasound for different purposes, serve as consolidating pillars for the importance of this tool for the progress of science and technology.…”
Section: Introductionmentioning
confidence: 99%